PENGARUH MEDIA SOSIAL PORNOGRAFI TERHADAP PERILAKU SEKSUAL REMAJA - Muhammad Doni Ramdani; Erna Ernawati; Febri Palupi Muslikhah (JURNAL SAHID DA'WATII, 2025)
Based on data KPAI in 2016 stated that 4500 teenagers accross 12 cities in Indonesia (97%) had spread seen pornographic shows. Many 60% of them are the students, they active watch speficifically for adults. Sexual behavior is all types of behavior which is caused by sexual desire, either with the opposite sex or with the same sex. The purpose of research to identify the influence of social media on teenagers sexual behavior in MTsS Anwarul Hidayah Pamijahan. The research was an analytical observational with cross sectional design. There are 71 respondents as a sample. The research instruments were questionnaires distributed through Google Forms. The results were analyze using SPSS with univariate and bivariate analysis (chi-square test). The result of the research showed there was influence between viewing frequency (p=0,001), viewing duration (p=0,001), viewing visualization (p=0,001), and perceptions of viewing (p=0,001) with adolescent sexual behavior.